Developing CDM Projects in the Western Balkans Legal and Technical Issues Compared - Montini, Massimiliano; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Developing CDM Projects in the Western Balkans: Legal and Technical Issues Compared, arises from the professional practical experience gained by an interdisciplinary team of legal and technical experts acting in the framework of the environmental bilateral cooperation performed by the Italian Ministry for the Environment, Land and Sea in the Western Balkan countries, through the "Task Force for Central and Eastern Europe". The volume is edited by Professor Massimiliano Montini, Director of the Environmental Legal Team (ELT) of the University of Siena, a group of young environmental lawyers and economists, in charge of providing the legal assistance for the implementation of the United Nations Framework Convention on Climate Change (UNFCCC) and the Kyoto Protocol (KP), as well as for paving the way for the development of the Clean Development Mechanism (CDM) projects in the Western Balkan countries. The added value of the book consists in the fact that it presents the real professional experience gained by a multi-sectoral team of lawyers, economists, engineers and other technical experts, working in synergy with a shared vision. This volume will be useful not only to those specifically interested in the Western Balkan area, but represents a broader example of lessons learned in the development of CDM projects. Therefore, it may have a broad market among Government officials and legal-economic-technical professionals dealing with climate change issues as well as academics developing scientific research in this field.
Legal Issues on the Kyoto Protocol and its Implementation Experiences in the Western Balkans -- The Kyoto Protocol in the International Environmental Law Context and the Post-2012 Scenario -- An Assessment of CDM: Lessons Learned and the Way Forward -- Carbon Market and Carbon Contracts for CERs Transactions -- The Designated National Authority (DNA): Requirements, Models, Competences, Best Practices -- DNAs Experiences in the Western Balkans: The Republic of Albania -- DNAs Experiences in the Western Balkans: The Republic of Macedonia -- DNAs Experiences in the Western Balkans: The Republic of Montenegro -- DNAs Experiences in the Western Balkans: The Republic of Serbia -- Technical Issues on the Kyoto Protocol and its Implementation Experiences in the Western Balkans -- The CDM Project Cycle -- The Identification of the CDM Potential in the Western Balkans Countries -- CDM Projects Experience in Albania -- CDM Projects Experience in Macedonia -- CDM Projects Experience in Montenegro -- CDM Projects Experience in Serbia -- Conclusion.
Keywords: Law; Comparative law; Public law; Climatic changes; Environmental law; Law; International & Foreign Law/Comparative Law; European Law/Public International Law; Climate Change; Environmental Law/Policy/Ecojustice.